Camphill and the Future Spirituality and Disability in an Evolving Communal Movement (Edition 1) - McKanan, Dan (University of California Press, 2020)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. The Camphill movement, one of the world's largest and most enduring networks of intentional communities, deserves both recognition and study. Founded in Scotland at the beginning of the Second World War, Camphill communities still thrive today, encompassing thousands of people living in more than one hundred twenty schools, villages, and urban neighborhoods on four continents. Camphillers of all abilities share daily work, family life, and festive celebrations with one another and their neighbors. Unlike movements that reject mainstream society, Camphill expressly seeks to be "a seed of social renewal" by evolving along with society to promote the full inclusion and empowerment of persons with disabilities, who comprise nearly half of their residents. In this multifaceted exploration of Camphill, Dan McKanan traces the complexities of the movement's history, envisions its possible future, and invites ongoing dialogue between the fields of disability studies and communal studies.